ANALYSIS OF STOMACH CONTENTS (MYSTUS NIGRICEPS, VALENCIANNES 1840) ON THE KAMPAR KIRI RIVER MENTULIK VILLAGE OF RIAU PROVINCE - Tata Ayu Cahyani; Roza Elvyra (Berkala Perikanan Terubuk, 2021)
Kampar River has a large diversity of fish fauna, one of which is the Mystus nigriceps in the Kampar KiriRiver. Fish is used by the community as a consumption and economic need. Increasing the need, makingfishermen catch fish continuously which results in a decrease in the population of fish in the river. Thepurpose of the study was to find out the type of natural food of Mystus nigriceps in the Kampar River KiriMentulik Village. Sampling in February-July 2021 from fishermen's catches using nets or tempirai andobservations were conducted at the Zoology Laboratory majoring in Biology. The results of the studyobtained the main food is insect, complementary foods are fish, and supplemental foods are not identified.Based on the data obtained, Mystus nigriceps is a type of carnivorous fish.